Tari Bayu Sutha Karya Anak Agung Anom Putra - Nayunda Nayunda; Anak Agung Ayu Mayun Artati; I Wayan Sutirtha (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2022)
Bayu Sutha Dance by Anak Agung Anom Putra The title of this study is Tari Bayu Sutha Karya Anak Agung Anom Putra. The purpose of this study is to find out the beginning of the creation, form and function of Bayu Sutha dance, to measure how far the author's ability to research or study a dance work, and provide information related to the beginning of the creation, shape and function of Bayu Sutha dance. In this study qualitative methods are used, to obtain complete data. The stages of data collection in this study, namely observation, interview, literature study, documentation study. The overall results of the data are processed and analyzed neatly and structured in order to get good results and appropriate conclusions from the research. Bayu Sutha dance is a dance creation that is danced singleally, created by Anak Agung Anom Putra. The dance was created as a request from the organizers of the International Gamelan Festival Amsterdam (IGFA) in the 100th anniversary event of the Tropen Museum Amsterdam on 9-11 September 2010. This Bayu Sutha dance tells the story of Hanoman's mercurial youth and has a sincere heart. Hanoman is the protagonist in the Ramayana story. Anak Agung Anom Putra was also inspired by his name